Lumbosacral Radiculopathy: A Case Report - Christianty Sugiarto; Amadea Jovita Miko Faustin; Hizkia; Leonardo Lionggono; Rickson Cuandre; Tria Ananda Putri (Medical Clinical Update, 2023)
Lumbar radiculopathy is a pathological process involving the lumbar radial nerve, especially theL5 and S1 radial nerve. This condition involved any cause of spinal nerve irritation, such as degenerative conditions of the spine, trauma, infection, tumors, and vascular abnormalities and manifestas radicular symptoms. Lumbosacral radiculopathy is a clinical diagnosis used to describe neurological symptoms due to secondary causes either mechanical and/or inflammatory involving oneof the lumbosacral nerve roots. At the age of 50 years and above, degenerative changes in thespine are the most causes of lumbar radiculopathy